2022
DOI: 10.3389/fphar.2021.785419
|View full text |Cite
|
Sign up to set email alerts
|

Applying Theory of Planned Behavior to Understand Physicians’ Shared Decision-Making With Patients With Acute Respiratory Infections in Primary Care: A Cross-Sectional Study

Abstract: Background: To understand the physicians’ shared decision-making behavior (SDM) with patients with acute respiratory infections (ARIs) based on the theory of planned behavior (TPB) and identify barriers to the implementation of SDM in primary care.Methods: A cross-sectional study of 617 primary care physicians was conducted in primary facilities in Hubei province, China from December 2019 to January 2020. A self-administered questionnaire based on TPB theory was applied for measuring the physicians’ SDM behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Previous evidence has shown that TPB can be used to understand health-related behaviours 18,19 and medical education. [20][21][22] Research has shown that in medical students, attitude and subjective norms predict behaviour intention, which is a signi cant predictor of shared decision-making behaviour. 20 Additionally, attitudes, subjective norms, and perception of behavioural control have been found to be important factors that in uence healthcare professionals' intention to engage in VBC practices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence has shown that TPB can be used to understand health-related behaviours 18,19 and medical education. [20][21][22] Research has shown that in medical students, attitude and subjective norms predict behaviour intention, which is a signi cant predictor of shared decision-making behaviour. 20 Additionally, attitudes, subjective norms, and perception of behavioural control have been found to be important factors that in uence healthcare professionals' intention to engage in VBC practices.…”
mentioning
confidence: 99%
“…[20][21][22] Research has shown that in medical students, attitude and subjective norms predict behaviour intention, which is a signi cant predictor of shared decision-making behaviour. 20 Additionally, attitudes, subjective norms, and perception of behavioural control have been found to be important factors that in uence healthcare professionals' intention to engage in VBC practices. 22 In this study, a cross-sectional survey with an online questionnaire was conducted among sixth-year medical students and postgraduate trainees in the Faculty of Medicine at…”
mentioning
confidence: 99%
“…Complex diagrams and numbers were not favoured as they were confusing to some. Tools such as patient information sheets and decision aids that contain relevant information can therefore assist patients in the decision process [ 13 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%